The Importance of Being Monogamous: Marriage and Nation Building in Western Canada in 1915 - Sarah Carter (The West Unbound:Social and Cultural Studies, 2008)
Sarah Carter reveals the pioneering efforts of the government, legal, and religious authorities to impose the "one man, one woman"model of marriage upon Mormons and Aboriginal people in Western Canada. This lucidly written, richly researched book revises what we know about marriage and the gendered politics of late 19th century reform, shifts our understanding of Aboriginal history during that time, and brings together the fields of Indigenous and migrant history in new and important ways.